DISPOSICIÓN DE BASURAS PRODUCIDAS EN LAS AULAS DE CLASE POR PARTE DE LOS ESTUDIANTES DE LA UNIVERSIDAD SANTO TOMÁS - Cotes Jurado, Alex Yesith; U. Santo Tomás (Universidad Santo Tomás Seccional Bucaramanga, 2012)
Objective: to describe how students in academic activities that develop at the Santo Tomas University manage the garbage in the classrooms on a daily basis.Methods: a descriptive cross sectional study was done in the classrooms at Santo Tomas University in Floridablanca. Classrooms, school hours, name of the building, day, week, semester, faculty, academic level, subject, number of class members, group, bottles, food wrappers, cups, paper, food waste, amount of garbage dumps in classrooms and in hallways, and distance to these deposits were evaluated. An univariate and bivariate analysis using statistical tests such as Chi square, Fisher exact test for qualitative variables and Student’s t test for quantitative variables were done.Results: one hundred thirty nine classrooms were evaluated 57.6% (80) reported the presence of garbage before starting classes and 82% (114) did after the academic session. The faculty that registered the highest increase of garbage after the classes end was physical culture with 69.2% (9).Conclusions: students from all semesters and all the faculties at the Santo Tomas University showed an improper handling of solid waste in the classroom and seemed to use very little the garbage dumps that were available in are in each room.